Impact of Trust and Service Quality on Retail Banking Customers' Satisfaction and Loyalty - G. Nagamani, Bhavishya Mathur, Renu Bala, Ganesh Datere, Akanksha Kathuria (Journal of Informatics Education and Research, 2024)
Banks are unable to rely solely on conventional service quality dimensions to drive customer satisfaction, despite the proven significance of service quality. This is one of the key insights from this study. Although dimensions such as assurance and reliability remain pertinent, they are insufficient in isolation to guarantee customer contentment in the current dynamic market. Customers are increasingly pursuing a combination of personalized experiences that make them feel appreciated and reliable, efficient digital services. It is imperative that banks maintain a balance between the human contact that fosters emotional connections and trust with customers and the provision of efficient digital services. This investigation investigates the influence of service quality and trust on customer satisfaction and loyalty in the retail banking industry. This analysis examines the impact of trust and the SERVQUAL model's dimensions—tangibility, reliability, responsiveness, assurance, and empathy—on customer satisfaction and loyalty, as determined by a survey of 145 respondents. The hypotheses were tested using statistical techniques such as regression analysis and correlation. The findings suggest that trust has a beneficial effect on customer satisfaction; however, the SERVQUAL dimensions do not have a significant impact on satisfaction. Banks are advised to enhance customer satisfaction and loyalty by enhancing service quality and fostering trust.